2018
DOI: 10.3390/foods7030041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Propolis Prepared in Different Forms and in Different Solvents Useful for Finished Products

Abstract: Different products from a unique propolis extract obtained by using various solvents such as hydroalcoholic, glycolic (98% propylene glycol), and glyceric solutions, and oil, as well as in powder form, named ESIT12, were prepared. The molecular composition of the different preparations was evaluated and their antioxidant activity determined. All the preparations showed a quite similar polyphenol composition and comparable percentage even if ESIT12 was found to be richer in phenolic acids (caffeic, coumaric, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
117
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 19 publications
2
117
1
2
Order By: Relevance
“…Moreover, it has been shown that pollen source greatly impacts the sensory characteristics, physicochemical properties (Dias, Pereira, & Estevinho, 2012) and phenolic composition of propolis (Moreira et al, 2008;Kalogeropoulos et al, 2009;Guzelmeric et al, 2018). The phenolic compounds, including phenolic acids and flavonoids, are highly associate with possibly beneficial effects on human health such as anti-inflammatory, immunological, antimicrobial, antitumor and antioxidant properties (Frasquet, & Sánchez, 2004;Viuda-Martos et al, 2008;Pratsinis et al, 2010;Galeotti et al, 2018). However, it has been demonstrated that pollen source also impacts the antiproliferative, antimicrobial and antioxidant activities (Guzelmeric et al, 2018;Pratsinis et al, 2010;Ristivojević et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that pollen source greatly impacts the sensory characteristics, physicochemical properties (Dias, Pereira, & Estevinho, 2012) and phenolic composition of propolis (Moreira et al, 2008;Kalogeropoulos et al, 2009;Guzelmeric et al, 2018). The phenolic compounds, including phenolic acids and flavonoids, are highly associate with possibly beneficial effects on human health such as anti-inflammatory, immunological, antimicrobial, antitumor and antioxidant properties (Frasquet, & Sánchez, 2004;Viuda-Martos et al, 2008;Pratsinis et al, 2010;Galeotti et al, 2018). However, it has been demonstrated that pollen source also impacts the antiproliferative, antimicrobial and antioxidant activities (Guzelmeric et al, 2018;Pratsinis et al, 2010;Ristivojević et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…After filtering, the procedure is repeated several times to assure a complete recovery of the active propolis component. The insoluble material is eliminated by filtration or centrifugation and the solvent is then evaporated to dryness under low pressure to reduce the extracted volume (Galeotti et al, 2017;Galeotti et al, 2018). The obtained solution is directly tested for molecular composition and biological activity.…”
Section: Sample Propolis Preparationmentioning
confidence: 99%
“…Current applications of propolis include preparations mainly based on extracts (ethanolic, water, glygeric, glycolic, oily or mix of this) and specific components may be selected during the extractive and preparative processes (Galeotti et al, 2017;Galeotti et al, 2018). These processes remove wax and other inert material and enrich the polyphenolic active compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also widely used in folk medicine. Propolis contains benzoic acid, cinnamic acid, phenols, ketophenols, hydroquinone, coumarins and naphthalene (Galeotti et al, 2018). www.food.actapol.net/ Chia seeds (Salvia hispanica) have become increasingly important worldwide due to their nutritious and functional properties.…”
Section: Introductionmentioning
confidence: 99%